Activation of BK Channel Contributes to PL-Induced Mesenchymal Stem Cell Migration - Echeverry, Santiago; Grismaldo, Adriana; Sánchez, Charles; Sierra, Cristian; Henao, Juan C.; Granados, Sara T.; Sutachán, Jhon-Jairo; Torres, Yolima P. (Frontiers in Physiology, 2020)
Due to their capacity to proliferate, migrate, and differentiate, mesenchymal stem cells (MSCs) are considered to be good candidates for regenerative medicine applications. The mechanisms underlying proliferation and differentiation of MSCs have been study. However, much less is known about the mechanisms regulating the migration of MSCs. Platelet lysate (PL), a supplement used to promote cell expansion, has been shown to promote MSCs migration; however the underlying mechanism are unknown. Here, by using adipose-derived rat MSCs (rMSCs) and the scratch assay in the absence and presence of various BK channels modulators, we evaluated the role of BK channels in mediating the PL-stimulated migration of rMSCs. We found that 5% PL increased rMSCs migration, and this effect was blocked by the addition of the BK channel selective antagonist Iberiotoxin (IBTX). In the absence of PL, the BK channel agonist NS1619, stimulated rMSCs migration to similar level as 5% PL. Addition of both NS1619 and PL resulted in an increase in rMSCs migration, that was higher than when either one was added individually. By using whole-cell recordings, it was found that the addition of PL increased the magnitude of BK current density. By using Western blot and flow cytometry, it was found that PL did not affect the expression of BK channels. Together, our results indicate that as shown in other cell types, activation of BK channels by themselves also promote rMSC migration, and show that activation of BK channels contribute to the observed PL-induced increase in migration of rMSC.